Prevalence and pattern of psychological disorders among key populations living with HIV/AIDS: findings from ECEWS supported global fund IMPACT project OSS centers in Southern Nigeria - Okezie Onyedinachi; Raphael Aguanunu; Grace Jimbo; Esther Essien; Andy Eyo; Rebecca Badejo; Ngozi Okeke; George Odutuga; Olufemi Oke (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2022)
Nigeria ranks third among countries with the highest burden of Human Immuno-Deficiency Virus (HIV) infection in the world. The 2019 Nigeria National HIV/AIDS Indicator and Impact Survey showed that 1.9 million people were living with HIV and AIDS in Nigeria as of 2018 [1].